Games Real Actors Could Play: The Problem of Complete Information - Fritz W. Scharpf (Max-Planck-Institut für Gesellschaftsforschung; Max-Planck-Gesellschaft zur Förderung der Wissenschaften e.V., 1989)
This contribution describes scientif ic associations in the FRG with regard to several social-structural variables - number, size, disciplinary distribution - and afterwards concentrates on the question which interests of members are served by these organizations. Four main interests are often mentioned: communicative interests within the respective research communities, individual and collective status interests, interests concerning the transfer between researchers and potential users of their knowledge, and, finally, interests with regard to influencing research policy. Empirically, communicative and transfer interests dominate today. – – Dieser Beitrag beschreibt wissenschaftliche Vereinigungen in der Bundesrepublik im Hinblick auf einige sozialstrukturelle Merkmale - Anzahl, Alter, Größe, disziplinäre Verteilung - und konzentriert sich dann auf die Frage, welche Mitgliederinteressen durch diese Typen von Organisationen bedient werden. Vier Hauptinteressen werden häufig genannt: Kommunikationsinteressen, individuelle und kollektive Statusinteressen, Transferinteressen im Sinne einer Kontaktvermittlung zwischen Forschern und potentiellen Nutzern ihrer Erkenntnisse und schließlich forschungspolitische Initiierungs- und Beratungsinteressen. Empirisch zeigt sich, daß gegenwärtig Kommunikations- und Transferinteressen im Vordergrund stehen.
Keywords: 300